2018
DOI: 10.1186/s12903-018-0630-3
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status, oral health and dental disease in Australia, Canada, New Zealand and the United States

Abstract: BackgroundSocioeconomic inequalities are associated with oral health status, either subjectively (self-rated oral health) or objectively (clinically-diagnosed dental diseases). The aim of this study is to compare the magnitude of socioeconomic inequality in oral health and dental disease among adults in Australia, Canada, New Zealand and the United States (US).MethodsNationally-representative survey examination data were used to calculate adjusted absolute differences (AD) in prevalence of untreated decay and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 38 publications
(35 reference statements)
4
44
0
2
Order By: Relevance
“…A lot of studies revealed that the prevalence of oral diseases is associated with socioeconomic status [7,9,33]. Education is the most common indicator used for the evaluation of socioeconomic differences in oral health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of studies revealed that the prevalence of oral diseases is associated with socioeconomic status [7,9,33]. Education is the most common indicator used for the evaluation of socioeconomic differences in oral health.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic factors are associated with oral health status. Individuals from lower income and education groups experienced poorer oral health and a higher burden of untreated oral diseases [ 7 , 8 , 9 ]. Socioeconomic differences in oral health may be related to differences in access to dental care because in many countries, a high proportion of dental care expenditure is out-of-pocket payments.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other countries, the prevalence of caries lesions in Australia shows a consistent social pattern [4]. Low socioeconomic factors and specific geographical areas have a strong association with high rates of dental caries, thereby increasing the plight of Indigenous children [3,[5][6][7]. Lack of water fluoridation is cited as part of the explanation for the high caries experience observed in children living in remote Indigenous communities [8].…”
Section: Introductionmentioning
confidence: 84%
“…Many factors impact caries risk, including saliva flow and composition, diet and nutrition, parental education, socioeconomics, age at transmission and acquisition of cariogenic species, oral hygiene, fluoride exposure, tooth anatomy, and enamel composition. [358][359][360][361][362][363][364][365][366][367][368] The tridimensional crystal structure of dental enamel is nonhomogeneous, differs between individuals, differs from tooth to tooth, and differs from site to site on the same tooth, thus influencing acid sensitivity. Furthermore, host genetics plays a determinant role.…”
Section: Dental Caries and Cariologymentioning
confidence: 99%